Invalidity of Hynobius yunanicus and molecular phylogeny of Hynobius salamander from continental China (Urodela, Hynobiidae) - Nishikawa, Kanto; Jiang, Jian-Ping; Matsui, Masafumi; Mo, Yun-Ming; Chen, Xiao-Hong; Kim, Jong-Bum; Tominaga, Atsushi; Yoshikawa, Natsuhiko (Zootaxa, 2010)
Based on morphological and molecular analyses, Xiong et al. (2007) synonymized Hynobius yunanicus Chen et al. with Pachyhynobius shangchengensis Fei et al., both from continental China. Their study, however, was not substantial enough in that morphology of types of neither species was compared, only a partial mitochondrial cytochrome b (cyt b) sequence was employed, and data for H. chinensis was lacking. In order to reassess their conclusion, we morphologically examined type specimens of both species, and compared their complete cyt b (1141 bp) sequences, together with all the six recognized continental Hynobius species and some congeners from Japan and South Korea.